2011
DOI: 10.1007/s00436-011-2600-4
|View full text |Cite
|
Sign up to set email alerts
|

First record of anisakid juveniles (Nematoda) in the European seabass Dicentrarchus labrax (family: Moronidae), and their role as bio-indicators of heavy metal pollution

Abstract: This study assessed the anisakid nematode distribution pattern in the fish collected from coasts of Mediterranean Sea, Egypt, during the period September 2010-April 2011. Two hundred thirty out of 300 (76.7%) Dicentrarchus labrax (European seabass) marine fishes belonging to family Moronidae were dissected and found to be infected with larva three nematodes. The larvae had been studied by light and scanning electron microscopy. The present work represents the first record of the presence of the parasite in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 36 publications
1
18
1
Order By: Relevance
“…In our study, in accordance, we found that Cr and Co were markedly higher in parasites than that in the host tissues. Morsy et al (2012) All trace elements accumulated at higher levels in parasites than in tissues of host, in accordance to the findings of some researchers (Azmat et al, 2008;Eira et al, 2009;Sures, 2003). Most studies of parasite bioaccumulation have used acanthocephalans as model organisms.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In our study, in accordance, we found that Cr and Co were markedly higher in parasites than that in the host tissues. Morsy et al (2012) All trace elements accumulated at higher levels in parasites than in tissues of host, in accordance to the findings of some researchers (Azmat et al, 2008;Eira et al, 2009;Sures, 2003). Most studies of parasite bioaccumulation have used acanthocephalans as model organisms.…”
Section: Discussionsupporting
confidence: 70%
“…This is in contrast with previous report showing that infested fish have lower levels of metals compared to non-infested fish from the same area (Azmat et al, 2008;Morsy et al, 2012). It is possible to argue that the amount of trace elements is expected higher in infested fish comparing to non-infested fish: since parasites compete with their hosts for nutrients, this would also lead to sharing of trace elements between host and parasite.…”
Section: Discussioncontrasting
confidence: 55%
“…Many studies were conducted on Anisakidae parasitizing Mediterranean fishes with high commercial value: Greece (Papoutsoglou 1975;Chaligiannisa et al 2012), Spain (Valero et al 2000;Valero et al 2006;Rello et al 2008;Gutiérrez-Galindo et al 2010), Italy (Larizza and Vovlas 1995), Egypt (Morsy et al 2012), and North African central Mediterranean coasts (Farjallah et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have also shown high prevalence of Anisakis spp. in salmonid species, and the worms were mostly found in the musculature or encapsulated on the visceral organs, mesenteries, and peritoneum (Smith 1984;Sugawara et al 2004;Noguera et al 2009;Morsy et al 2012).…”
Section: Discussionmentioning
confidence: 99%